P4.79 The distribution of sex partners in the united states by sexual identity: data from the national survey of family growth. (8th July 2017) - Dittus, Patricia; Beltran, Oscar; Haderxhanaj, Laura; Leichliter, Jami; Chesson, Harrell; Aral, Sevgi
Abstract : Introduction: Risky sexual behaviour and STIs cluster within subpopulations. Examining the concentration of behaviours can help to target interventions to those at highest risk. Given STI disparities by sexual identity, we examined the distribution of sexual partners among heterosexual, homosexual, and bisexual males and females. Methods: Data from the 2006–15 U.S. National Survey of Family Growth were used to analyse the number of opposite-sex and same-sex partners in the past 12 months, focusing on means and the percentage of sex partners accounted for by the top 20% of each subpopulation; 95% confidence intervals were used to examine significant differences. Demographics will also be reported. Results: Bisexual women reported a higher mean number of recent opposite-sex partners (1.81; 95% CI: 1.66, 1.96) than heterosexual (1.21; 95% CI: 1.19, 1.24) and homosexual (0.79; 95% CI: 0.26, 1.32) women, whereas homosexual women reported a higher number of same-sex partners (1.55; 95% CI: 1.39, 1.72) than bisexual (0.74; 95% CI: 0.64, 0.84) and heterosexual women (0.21; 95% CI: 0.17, 0.25). Within each subgroup, the top 20% of bisexual and heterosexual women accounted for 45% and 37.6% of opposite-sex partners, respectively. Among males, there was no difference in the mean number of recent opposite-sex partners between heterosexual and bisexual men (1.5 partners), whereas homosexual men reported a significantly higher mean number of recent same-sex partners (2.39; 95% CI: 2.11, 2.67) than bisexual (1.16; 95% CI: 0.87, 1.45) and heterosexual men (0.18; 95% CI: 0.12, 0.24). Within each subgroup, the top 20% of heterosexual men accounted for 47.1% of opposite-sex partners compared to the top 20% of gay and bisexual men accounting for 48.1% and 59.8% of same-sex partners, respectively. Conclusions: In general, sexual minorities reported higher numbers of recent sex partners, however, interesting gender differences emerged, particularly with regard to the top 20% of subpopulations. Interventions targeting high-risk persons within sub-populations may be more impactful.